Ocean‐Scale Interactions From Space. Issue 5 (22nd May 2019) - Klein, Patrice; Lapeyre, Guillaume; Siegelman, Lia; Qiu, Bo; Fu, Lee‐Lueng; Torres, Hector; Su, Zhan; Menemenlis, Dimitris; Le Gentil, Sylvie
Abstract : Satellite observations of the last two decades have led to a major breakthrough emphasizing the existence of a strongly energetic mesoscale turbulent eddy field in all the oceans. This ocean mesoscale turbulence is characterized by cyclonic and anticyclonic eddies (with a 100‐ to 300‐km size and depth scales of ∼500–1, 000 m) that capture approximatively 80% of the total kinetic energy and is now known to significantly impact the large‐scale ocean circulation, the ocean's carbon storage, the air‐sea interactions, and therefore the Earth climate as a whole. However, ocean mesoscale turbulence revealed by satellite observations has properties that differ from those related to classical geostrophic turbulence theories. In the last decade, a large number of theoretical and numerical studies has pointed to submesoscale surface fronts (1–50 km), not resolved by satellite altimeters, as the key suspect explaining these discrepancies. Submesoscale surface fronts have been shown to impact mesoscale eddies and the large‐scale ocean circulation in counterintuitive ways, leading in particular to up‐gradient fluxes. The ocean engine is now known to involve energetic scale interactions, over a much broader range of scales than expected one decade ago, from 1 to 5, 000 km. New space observations with higher spatial resolution are however needed to validate and improve these recent theoretical and numerical results. Key Points: Twenty‐five years of satellite altimeter observations and recent numerical studies highlight that all the oceans are fully turbulent This turbulence involves energetic ocean‐scale interactions over a broad range of scales, from 1 to 5, 000 km These interactions control the ocean kinetic energy budget, heat storage, biodiversity, and air‐sea exchanges